2013
DOI: 10.1242/jcs.135509
|View full text |Cite
|
Sign up to set email alerts
|

A non-canonical role for Rgnef (p190RhoGEF) in promoting integrin-stimulated focal adhesion kinase activation

Abstract: SummaryRgnef (also known as p190RhoGEF or ARHGEF28) is a Rho guanine-nucleotide-exchange factor (GEF) that binds focal adhesion kinase (FAK). FAK is recruited to adhesions and activated by integrin receptors binding to matrix proteins, such as fibronectin (FN). Canonical models place Rgnef downstream of integrin-FAK signaling in regulating Rho GTPase activity and cell movement. Herein, we establish a new, upstream role for Rgnef in enhancing FAK localization to early peripheral adhesions and promoting FAK acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…FAK recruitment and activation at nascent FAs involves binding to the Rho guanine nucleotide exchange factor (GEF) ARHGEF28 (p190RhoGEF or Rgnef), and a FAK-ARHGEF28 signaling complex promotes local invasion of orthotopic colon carcinomas in mice 47, 48 . FAK-ARHGEF28 dimerization and the associated increase in FAK activation is thereby linked to elevated tyrosine phosphorylation of paxillin, an adaptor protein involved in FA maturation 49 .…”
Section: Fak In Tumor Cellsmentioning
confidence: 99%
“…FAK recruitment and activation at nascent FAs involves binding to the Rho guanine nucleotide exchange factor (GEF) ARHGEF28 (p190RhoGEF or Rgnef), and a FAK-ARHGEF28 signaling complex promotes local invasion of orthotopic colon carcinomas in mice 47, 48 . FAK-ARHGEF28 dimerization and the associated increase in FAK activation is thereby linked to elevated tyrosine phosphorylation of paxillin, an adaptor protein involved in FA maturation 49 .…”
Section: Fak In Tumor Cellsmentioning
confidence: 99%
“…Moreover, emerging evidence supports the importance of Rgnef-FAK interactions in promoting tumor progression [37]. In this review, we will expand upon a novel concept that Rgnef also functions as a scaffold in a GEF-independent manner to enhance FAK activation downstream of integrins [38] and how this may impact tumor biology.…”
Section: Rgnef (P190rhogef/arhgef28) and Fakmentioning
confidence: 99%
“…30 Furthermore, more recent work has suggested that p190RhoGEF is required for proper FAK localization to peripheral adhesions in mouse embryonic fibroblasts. 31 Thus, it may be interesting to investigate a role for other GEFs in directional EC signaling in response to shear stress in future studies.…”
Section: Polarization Of Rac1 Activitymentioning
confidence: 99%